Outcome and prognostic factors in nonambulatory Hansen Type I intervertebral disc extrusions: 308 cases - Ruddle, T. L.; Allen, D. A.; Schertel, E. R.; Barnhart, M. D.; Wilson, E. R.; Lineberger, J. A.; Klocke, N. W.; Lehenbauer, T. W. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Thoracolumbar intervertebral disc disease is the most common cause of caudal paresis in dogs (1). Whilst the pathogenesis of the extrusion has been widely studied, treatment protocols and prognostic factors relating to outcome remain controversial. Recent studies have examined a multitude of factors relating to time to regain ambulation after decompressive surgery. Most intervertebral disc herniations occur in the thoracolumbar region, causing upper motor neuron signs in the rear limbs, which are thought to have a more favourable prognosis compared to the lower motor neuron signs created by herniation of an intervertebral disc in the caudal lumbar region. Due to the potential disruption of the lumbar intumescence, lower motor neuron signs have been reported as having a less favourable prognosis. The purpose of this study was to evaluate the intervertebral disc space as a prognostic factor relating to ambulatory outcome and time to ambulation after decompressive surgery. Hansen Type I intervertebral disc extrusions were studied in 308 non-ambulatory dogs. Preoperative and postoperative neurological status, corticosteroid use, signalment, intervertebral disc space, postoperative physical rehabilitation, previous hemilaminectomy surgery, disc fenestration, return to ambulation, and time to ambulation were reviewed.
Keywords: Intervertebral disc herniation; time to ambulation; dogs